Correlation of serum‐ and glucocorticoid‐regulated kinase 1 expression with ischemia–reperfusion injury after heart transplantation. (17th December 2014) - Yang, Xuechao; Wu, Xiang; Wu, Kunpeng; Yang, Dunpeng; Li, Yangcheng; Shi, Jiahai; Liu, Yonghua
Abstract IRI of a transplanted heart may result in serious early and late disadvantageous effects such as increased allograft immunogenicity, primary graft dysfunction, and initiation of fibroproliferative cascades that compromise the survival of the recipient. Sgk‐1 has recently been linked to cell growth and survival. It has been reported that through a renal transplantation model, Dexa increases Sgk‐1 expression and therefore protects from renal IRI. In our current study, we aim to assess the expression of Sgk‐1 and its protective effects on cardiomyocyte IRI after heart transplantation. Heart allograft model was performed from Wistar into Lewis, and isograft model was from Lewis into Lewis. Grafts were then harvested at one, six, 12, or 24 h post‐transplantation for Sgk‐1 expression analyses. In some groups, part donors were treated with Dexa 2 h prior at doses of 0.05, 0.5 and 2 mg/BWkg, respectively. Sgk‐1 expression was markedly increased in grafted heart 6–12 h post‐transplantation in both the allogenic and isogenic models. Immunostaining experiments confirmed that Sgk‐1 was expressed in cardiomyocytes rather than infiltrated immune cells. Furthermore, Dexa treatment significantly increased Sgk‐1 expression and the donor cardiomyocyte injury was greatly minimized by Dexa treatment. These results suggest that induction of Sgk‐1 might explain some of the beneficial impact of corticosteroids in IRI and hence might have therapeutic implications.